Experimental Music Composition “Rhythm Flower” | Komposisi Musik Eksperimental “Rhythm Flower” - I Made Prayoga Adi Astawa; I Ketut Partha (GHURNITA: Jurnal Seni Karawitan, 2023)
The composer's goal is to realize an idea that is owned by the composer himself through a compositional work based on experimental interests. Rhythm Flower's experimental composition work is a work that focuses on the processing of rhythm, meaning that all the processing that is carried out arises from a rhythm pattern that is used as a reference. Because of this, the composer uses instruments that are classified as rhythmic instruments, namely drums and reongs, as well as the addition of a gong instrument as an affirmation of the size of the rhythm pattern in it. The experiments carried out included processing the workings of patterns, percussion instruments, and how to play instruments. This processing resulted from a creative process borrowed from the concept of Pande Made Sukerta, namely compiling content ideas, compiling ideas, and determining work. The processing is then organized into three different parts, namely parts one, two, and three. These three parts have different impressions and intentions between parts one to part three. Starting from part one which is still processing conventionally, part two which has begun to show experiments on how to play the reversed reong, and part three which focuses on experimenting with the use of drum sticks on drum instruments.